Variability and connectivity in populations of different limpet species across rockpool-generated mosaic landscapes - Seabra, Maria Inês; Penteado, Nélia; Cruz, Teresa; Hawkins, Stephen J. (Frontiers in Marine Science, 2023)
Limpets are keystone grazers within rocky-intertidal communities. Here we studied spatial patterns of four co-occurring patellids (Patella ulyssiponensis, P. depressa, P. rustica and P. vulgata) and one siphonariid (Siphonaria pectinata) across rockpool-generated mosaic landscapes. Our approach considered each rockpool as a concentric system of three micro-habitats where limpets were censused (species, counts and size of individuals): inside-rockpool; edge-zone; and surrounding open-rock. The whole intertidal gradient was sampled on six rocky-shores with contrasting landscape variability (relative availability of open-rock and topographic micro-habitats) in Southwest Portugal. Additionally, open-rock surfaces far (> 25cm) away from rockpools were surveyed on the mid-shore. Three groups of predictors (“physical; habitat-composition; and connectivity variables”) were assessed for each rockpool-system. Patella vulgata was rare; P. rustica was absent from rockpools and their edges. Limpets of various sizes of the three most common species – P. ulyssiponensis, P. depressa and S. pectinata – were found to coexist inside and outside rockpools on all shores, with rockpools extending their vertical distribution upwards. A decreasing gradient of intra-specific connectivity (correlations in density of the same species between adjacent micro-habitats) was sharp in the largely rockpool-resident P. ulyssiponensis, suggesting more gradual emergence from rockpools to their edges and surrounding open-rock in P. depressa and S. pectinata. Abundance and size-structure of both P. depressa and S. pectinata were similar on mid-shore open-rock surrounding rockpools and far away from rockpools. Landscape variability was associated with the distribution of P. depressa (shores with less open-rock had more and smaller limpets). Habitat-composition (assemblages and substrata) was more important than physical predictors in explaining among-rockpool variability of each limpet species. Densities of P. ulyssiponensis and P. depressa inside-rockpools were positively associated with cover of coralline algae and negatively associated with sand cover. Less explanatory power was found in predictive models of S. pectinata, suggesting a more opportunistic nature. There was lack of evidence of inter-specific or intra-specific competition of the three species in rockpools and open-rock. Competition between P. ulyssiponensis and P. depressa was only likely in rockpool-edges. Rockpool-generated mosaic landscapes are linked by intra-specific connectivity of limpet populations and modulated by interactions among different limpet species.